LAS INDUSTRIAS AZUCARERA Y PETROLERA EN EL ZULIA: FORMAS DE OCUPACIÓN TERRITORIAL (1913-1930) - Rodríguez Arrieta, Marisol (2012)
This article aims to explain the different forms of land appropriation and occupation in the eastern and southern regions of Zulia state, located in western Venezuela. Creole and foreign capitalists, through joint-stock companies, invested in the sugar and oil industries, quickly monopolizing large territories for their exploration and exploitation. Although these two industrial processes unfolded at different historical moments and involved different social actors, they occurred within similar timeframes. Industrialization required vast tracts of land, which corporate leaders acquired and transformed through purchases, negotiations, contracts, removals, and even expropriations of lands, homes, livestock, and agricultural properties—both public and private. These actions were facilitated by the legal framework of the time and by alliances with local municipalities and the government of General Juan Vicente Gómez. The companies’ freedom and strong political support allowed them to reshape traditional infrastructure to suit corporate needs. For the first time in Venezuela, modern equipment and machinery were introduced, operated by skilled personnel and a large labor force. The study uses the historical method as a scientific tool to analyze these dynamics.